Carbon Deposition over Ni/ZrO2 Catalyst for Dry Reforming of Methane Reaction - Boonsrisod , Nattaphong; Phongaksorn, Monrudee; Tungkamani, Sabaithip; Ratana, Tanakorn (Burapha Science Journal, 2024)
Background and Objectives : The increase of greenhouse gases (carbon dioxide and methane) in recent decades has led to a global warming crisis. As a result, researchers are interested in solving this problem. Dry reforming of methane (DRM) is an attractive reaction for syngas production (hydrogen and carbon monoxide) from greenhouse gases. The nickel-based catalysts are often used as catalysts in DRM reaction, because of their high activity and low cost. However, there is also a disadvantage to the carbon deposition, leading to the catalyst deactivation. ZrO2 has been considered an attractive support due to its good resistance to coke formation. Therefore, this work is interested in studying the formation of carbon deposits on various Ni/ZrO2 catalysts. Methodology : The Ni(NO3)2 solution was deposited on ZrO2, which is prepared in four different ways with 10% Ni loading by the impregnation method. The physico-chemical properties of supports and catalysts were analyzed by XRD, N2 adsorption-desorption, and H2-TPD techniques. The type and amount of the deposited carbon on the spent 10% Ni/ZrO2 catalysts were characterized by XRD, O2-TPD and TEM techniques. Main Results : Four ZrO2 samples with different microstructure and morphology were used as catalyst support. The catalytic performance of 10%Ni/ZrO2 catalysts conducted in fixed-bed reactor DRM reaction was found the different catalytic activity of different catalysts. Conclusions : It was found that the effects of Ni particle size and zirconia phase had a significant influence on the catalytic activity. Moreover, both the type and amount of carbon deposition on spent Ni/ZrO2 were also related to the catalytic activity.